Metabolism Profile of Mequindox in Sea Cucumbers In Vivo Using LC-HRMS - Xin Mao; Xiaozhen Zhou; Jun He; Gongzhen Liu; Huihui Liu; Han Zhao; Pengjie Luo; Yongning Wu; Yanshen Li (MDPI AG, 2022)
In this work, the metabolism behavior of mequindox (MEQ) in sea cucumber in vivo was investigated using LC-HRMS. In total, nine metabolites were detected and identified as well as the precursor in sea cucumber tissues. The metabolic pathways of MEQ in sea cucumber mainly include hydrogenation reduction, deoxidation, carboxylation, deacetylation, and combinations thereof. The most predominant metabolites of MEQ in sea cucumber are 2-iso-BDMEQ and 2-iso-1-DMEQ, with deoxidation and carbonyl reduction as major metabolic pathways. In particular, this work first reported 3-methyl-2-quinoxalinecarboxylic acid (MQCA) as a metabolite of MEQ, and carboxylation is a major metabolic pathway of MEQ in sea cucumber. This work revealed that the metabolism of MEQ in marine animals is different from that in land animals. The metabolism results in this work could facilitate the accurate risk assessment of MEQ in sea cucumber and related marine foods.